2016
DOI: 10.1095/biolreprod.116.141804
|View full text |Cite
|
Sign up to set email alerts
|

The Unfolded Protein Response Regulates Uterine Myocyte Antioxidant Responsiveness During Pregnancy

Abstract: There is considerable evidence that implicates oxidative stress in the pathophysiology of human pregnancy complications. However, the role and the mechanism of maintaining an antioxidant prosurvival uterine environment during normal pregnancy is largely unresolved. Herein we report that the highly active uterine unfolded protein response plays a key role in promoting antioxidant activity in the uterine myocyte across gestation. The unfolded protein response (UPR) senses the accumulation of misfolded proteins i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…It was found that genes Eif2ak3 and Eif4g1 both decreased as gestation proceeded. In the absence of Eif2AK3 , other studies have found cells to experience increased oxidative stress, leading to cell death ( Ramnarayanan et al 2016 ). Although this study did not measure markers of oxidative stress directly, we indirectly established increases in superoxide production across gestation through decreases in the antioxidant activity of SOD, which may indicate that there was an increase of ROS at E16.5.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that genes Eif2ak3 and Eif4g1 both decreased as gestation proceeded. In the absence of Eif2AK3 , other studies have found cells to experience increased oxidative stress, leading to cell death ( Ramnarayanan et al 2016 ). Although this study did not measure markers of oxidative stress directly, we indirectly established increases in superoxide production across gestation through decreases in the antioxidant activity of SOD, which may indicate that there was an increase of ROS at E16.5.…”
Section: Discussionmentioning
confidence: 99%
“…It plays a critical role in neutralizing oxidative stress by activating the expression of antioxidants and detoxifying enzymes [ 45 ]. The activation of EIF2AK3 and GSTT1 genes is associated with decreased level of reactive oxygen species [ 46 , 47 ]. Previously, the augmentation of the NRF2-mediated oxidative stress response pathway is observed in breast muscle of higher feed efficient and rapidly growing chickens [ 48 ].…”
Section: Discussionmentioning
confidence: 99%